Epoxidized natural rubber-based nanostructured polymer blends / Chan Chin Han - Chan, Chin Han (Research Management Institute (RMI), 2010)
Blends of poly(3-hydroxybutyrate-<?0-3-hydroxy valerate) (PHBV) with 12 mol% hydroxy valerate (HV) content and epoxidized natural rubber (ENR) with 50 mol% epoxidation level were studied along with the thermal properties and morphologies. Glass transition temperatures reveal immiscibility of the polymers over the entire composition range. The equilibrium melting point (Tm°) of PHBV in blends was determined applying Hoffman-Weeks step-wise annealing procedure. There is no significant variation of Tm° for PHBV with blend composition. Also the crystallinity of PHBV stays approximately constant in the blends, only a slight decrease might be recognized with increasing ENR content. The rate of crystallization of PHBV decreases with PHBV content according to a power law. Morphological studies by polarizing optical microscopy reveal a fine intraspherulitic dispersion of ENR in volume-filling PHBV spherulites, which develop during isothermal crystallization.